OVARIAN RESERVE FOR PATIENTS INCLUDED IN EXTRACORPORAL FERTILIZATION PROGRAMS - Мария Сергеевна Сворова; Елена Николаевна Кравченко; Людмила Геннадьевна Макаркина; Галина Владимировна Кривчик; Татьяна Владимировна Ковешникова; Кирилл Петрович Кропмаер (The Publishing House Medicine and Enlightenment, 2018)
Objective - to study the ovarian reserve and to identify the effectiveness of IVF programs in women of different age categories. Material and methods:. The study included 241 patients from the Department of VRT at the City Clinical Perinatal Center, which inducted superovulation in IVF and PE programs in 2016. All women were divided into 4 age groups. I group up to 30 years were 60 people (25 %), II group 31-35 years - 85 people (35 %), III 36-39 years - 61 people (25 %), IV groups over 40 years - 35 people (15 %). In these groups, the parameters of the ovarian reserve (AMG, the number of antral follicles), the response to stimulation of superovulation (the number of oocytes obtained during transvaginal puncture of follicles) and the effectiveness of IVF programs (biochemical and clinical pregnancy) were analyzed. Results. In the comparative analysis of the AMH level, the low value (less than 1.0 ng/ml) in the IV group was significantly higher (in 24 women - 69 %) in group I (4 patients - 7 %, p <0.005). In a comparative analysis of the number of antral follicles in the ovaries, their small number (less than 5) was detected in 26 women of the IV group (75 %), versus 4 people (6 %) of the I group (p <0.005). In women less than 5 years after the age of 40, transvaginal puncture was significantly more frequent than in other age groups: 23 women (71 %) - IV group, 11 women (18 %) - I group (p <0.005). Positive results of IVF and PE programs were significantly lower in the IV age group compared to the rest. Clinical pregnancy in group IV was registered in only 3 women (9 %), in group I in 25 patients (41 %). The conclusion. The age of the woman, the level of AMH, the number of antral follicles can serve as reliable markers in determining the individual ovarian reserve and be taken into account for predicting the effectiveness of the IVF and PE program. With age, the effectiveness of the IVF and PE program is progressively decreasing and reaches a minimum after 40 years.